Exploring personality and fit for garden festivals and parks: a Best-Worst Scaling approach - Quintal, Vanessa; Soutar, G.; Phau, Ian; Sood, Abhinav (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
The current study explores the personality attributes and fit between garden festivals and parks that host them. The research adopted a bottom-up approach, inviting stakeholder participation in six focus groups, two expert panels, a pilot study and three main studies to examine Araluen Botanic Park, Western Australia as well as its Chilli Festival and Tulip Festival. A total of 878 completed surveys were collected. The personality attributes of the Chilli Festival identified as being Contemporary and Competent, and the Tulip Festival, as being Tranquil. Both garden festivals shared the Genuine attribute, demonstrating some personality fit. However, the personality attributes of the park remained undetermined. By adopting the theoretical underpinnings of the Brand Personality Scale (BPS) and the methodological approach of Best-Worst Scaling (BWS) to identify the personality attributes, the study presents a framework to access much needed information effectively. The information guides pragmatic branding strategies for differentiating and creating connections with visitors.